Pengaruh Persepsi Risiko terhadap Kepercayaan Merek PT Sang Hyang Seri Padangsidimpuan - Agusta Linda Nora; Fithra Maharani; Elwin Kurniawan (CV. ITTC INDONESIA, 2026)
This study aims to evaluate the extent to which perceived risk influences brand trust among customers of PT Sang Hyang Seri Padangsidimpuan. The study adopts a quantitative methodology with an associative research framework to investigate the relationship between perceived risk as an explanatory variable and brand trust as the outcome variable. The research population includes 400 customers, with 40 respondents selected through purposive sampling based on predetermined criteria. Primary data were collected through questionnaires employing a five-point Likert scale and analyzed using simple linear regression supported by IBM SPSS Statistics. The empirical findings indicate that perceived risk has a significant positive impact on brand trust. The regression estimation shows a coefficient of 0.482, while the t-statistic of 4.407 is higher than the t-critical value of 1.686, confirming the significance of the proposed relationship. The R² value of 33.8% indicates that perceived risk contributes to explaining variations in brand trust, whereas the remaining 66.2% is attributed to other variables outside the research model. The findings suggest that strengthening product assurance, reducing customer uncertainty, and maintaining consistent service performance are essential strategies for enhancing brand trust in the agribusiness sector.